Immunotherapy With Recombinant Alt a 1 Suppresses Allergic Asthma and Influences T Follicular Cells and Regulatory B Cells in Mice - Liu, Juan; Yin, Jia (Frontiers in Immunology, 2021)
Background: Alternaria is a major source of asthma-inducing allergens. Allergen-specific immunotherapy improves the progression of allergic asthma. The current treatment is based on crude Alternaria extracts. Alt a 1 is the predominant allergen in Alternaria. However, the treatment efficacy of recombinant Alt a 1 (rAlt a 1) in an asthmatic animal model and its influence on Tfh and Breg cells are unknown. Objective: To explore the therapeutic treatment effects of rAlt a 1 on the progress of an asthmatic mouse model and its effect on Tfh and Breg cells. Methods: We synthesized and purified rAlt a 1. Alternaria-sensitized and challenged mice received subcutaneous immunotherapy (SCIT) with four different rAlt a 1 dosage (5, 50, 100, and 150 µg) or PBS only. Finally, lung and airway inflammation, mouse mast cell protease 1 (MMCP-1), serum immunoglobulin responses, Tfh and Breg cell levels, and the correlation between asthmatic features (inflammation grades and IL-4 and IL-10 levels) and these two cell types were measured after Alternaria re-challenge. Results: High purity and allergenic potency of rAlt a 1 protein were obtained. Following treatment with four different rAlt a 1 dosages, both lung and airway inflammation ameliorated, including lung pathology, serum MMCP-1 levels, inflammatory cell numbers, and cytokine levels in bronchoalveolar lavage fluid (BALF). Additionally, rAlt a 1-SCIT increased the expression of Alternaria-sIgG1, rAlt a 1-sIgG1, rAlt a 1-sIgG2a, and rAlt a 1-sIgG2b in serum. Moreover, the percentage of Tfh cells decreased when Breg cells were evaluated after administration of rAlt a 1. A positive correlation was observed between Tfh cells and inflammation grades and IL-4 and IL-10 levels; Breg cells showed an opposite correlation. Conclusions: We verified that treatment with rAlt a 1 can alleviate asthma progression and further have a regulatory effect on Tfh and Breg cells in an Alternaria-induced asthmatic mouse model.